2021
DOI: 10.1111/jfpp.16137
|View full text |Cite
|
Sign up to set email alerts
|

Study of physicochemical, nutritional, and anticancer activity of Murraya Koenigii extract for its fermented beverage

Abstract: Murraya koenigii L (Curry) leaves, known for its natural polyphenols, possess efficient antioxidant properties that maintain oxidative stress and promote health benefits. Higher content of phenolics (77.00 µg GAE/mg) and flavonoids (21.02 µg RU/mg) was detected in M. koenigii leaves extract along with ultra‐performance liquid chromatography quantification (UPLC) followed by antioxidant activity. The extract exhibited competent anti‐cancer activity against A549 and CHOK1 carcinoma cell lines. Therefore, M. koen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The essential oil of M. koenigii showed an antimicrobial effect against B. subtilis, S. aureus, and P. vulgaris and an antifungal effect against C. albicans, C. tropicalis, A. niger, and A. fumigates [109]. In recent studies, the high abundance of phenolic compounds and flavonoids isolated from M. koenigii, administrated in the form of a fermented beverage, led to a rapid increase in protein and amino acid contents, which could be exploited in anticancer treatments [110]. In the food industry, M. koenigii leaf extracts have demonstrated their high potential for use as probiotics [27] and as bio-preservatives for fruit juice [21] or food additives [111].…”
Section: Compounds Active Principles and Industry Importance Of The L...mentioning
confidence: 99%
“…The essential oil of M. koenigii showed an antimicrobial effect against B. subtilis, S. aureus, and P. vulgaris and an antifungal effect against C. albicans, C. tropicalis, A. niger, and A. fumigates [109]. In recent studies, the high abundance of phenolic compounds and flavonoids isolated from M. koenigii, administrated in the form of a fermented beverage, led to a rapid increase in protein and amino acid contents, which could be exploited in anticancer treatments [110]. In the food industry, M. koenigii leaf extracts have demonstrated their high potential for use as probiotics [27] and as bio-preservatives for fruit juice [21] or food additives [111].…”
Section: Compounds Active Principles and Industry Importance Of The L...mentioning
confidence: 99%
“…However, the leaf extract contained remarkable anti-cancer property against CHOK1 and A549 cancer cell lines. [65] Anti-diabetic, and anti-aging effect [145] Aqueous extract Leaves -…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Bhatt et al observed that leaf extract of M. koenigii contained higher amount of total phenolics content of 77.00 μg GAE/mg and even total flavonoid content of 21.02 μg RU/mg using ultra‐performance liquid chromatography quantification and this shows that the leaf extract possess significant antioxidant property. However, the leaf extract contained remarkable anti‐cancer property against CHOK1 and A549 cancer cell lines [65] …”
Section: Pharmacological Activitiesmentioning
confidence: 99%